(3geY GdghGeY aj TQM LeY GdLhGeYs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3hHYO, aEf dfG JCdjakG aj GdYQHjI LeY COfGgG hCbUGgG hLeYJg ef fMh eFI eUfa s
(3BNQgG (B:s
(3aOhfc eNJUQG GfWhi Ydi RHOI eFI eUfa hCJi ef GdYLH GdYLGH HeG de jLeYg bHdg eDda gcPG HCUd GdeDda QMeg Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3GdfMhs